KONSEP MASHLAHAH MURSALAH NAJM AL-DIN AL-THUFI - Supriadi, Lalu (JURNAL PENELITIAN KEISLAMAN, 2012)
Mas}lah}ah mursalah as a method experiencing internal problems related to designation of meaning of the character of the text that is âsketchyâ as well as externally as âtemptationâ faced by the mujtahid thus providing excessive portion of reasons result in the law established considered to be not in line with the spirit of Shariâah itself. One of the scholars who actively studied this field was Najm al-Di>n al-T}u>fi. Through methods of library research, some works of Najm al-Di>n al-T}u>fi had found out that, according to al- T}u>fi sources of Islamic law which is the most powerful in the hierarchy is legal nas (the text of the Qurâan and Hadith) and ijma`. If both (texts and ijma) stated the law which is in line with the meaning and spirit formulated by mas}lah}ah mursalah then no problem arise, however if there is a conflict (texts and ijma `versus mas}lah}ah mursalah), then mas}lah}ah mursalah should take precedence (priority) with takhshis way (specialized meaning of one of them) and bayÃ¢n (explaining the meaning of one of them), not by denying or neglecting it at all. As occurs in as-Sunna, a source of law can take precedence over the Qurâan using bayÃ¢n method. It happened because mas}lah}ah (benefit) is the ultimate goal of the application of Islamic rulesâ against mukallaf, while the other sources of law in Islam is the means by which to understand the purpose.